Critical Analysis of the Rejection of Richard Bell's Thoughts on the Translation of the Qur'an in the Context of Orientalism - Ilham Abiyusuf; Muhammad Hafizi; Pakhrurrozi Pakhrurrozi; Wahyu Saputra; Edi Hermanto (Yayasan Adra Karima Hubbi, 2024)
Background. Richard Bell, a prominent English orientalist, applied historical, linguistic, and critical analysis to study the Qur'an in its historical and cultural contexts. However, his approach faced rejection from Muslim scholars, who argue that Bell's method fails to capture the Qur'an's true meaning as divine revelation. Purpose. This study examines the rejection of Richard Bell's approach by Muslim scholars and scientists, aiming to understand the key arguments behind their opposition and evaluate its alignment with Islamic principles of Qur'anic interpretation. Method. A qualitative approach is used, employing document analysis to review literature on Bell's works and methods, as well as texts outlining the views of Muslim scholars on Qur'anic interpretation. The analysis focuses on identifying the points of rejection and evaluating the reasoning behind them. Results Muslim scholars reject Bell's approach because they believe it lacks respect for the Qur'an as divine revelation. They argue that his focus on historical criticism overlooks the context of revelation and Prophet Muhammad's explanations. They see the Qur'an as a unified whole and question the applicability of Western academic methods to understanding religious texts. Ultimately, they find Bell's approach incompatible with Islamic principles of interpretation. Conclusion. Muslim scholars reject Richard Bell's historical and critical methods, asserting that these approaches are insufficient to grasp the true meaning of the Qur'an as a sacred text.